Development and deployment of an adaptive national elementary reading screening test - Walgermo, Bente Rigmor; Foldnes, Njål; Uppstad, Per Henning; Bakken, Arild Michel; Lundetræ, Kjersti (Frontiers in Education, 2024)
Increasingly over the past decade, there has been a demand of more thorough documentation of the quality of reading assessments. Yet, available documentation of high-quality measures are often restricted to general framework descriptions providing psychometric information as a token of test quality. In a modern view of validity, understanding what is being measured and how scores are calculated is a prerequisite for good interpretation and use of test scores. The present article aims to document the research and development process of a national adaptive screening test for reading difficulties, in which the envisioned interpretation and use of test scores is guiding the work. Given the mandatory nature of this test the sample consist of 49,828 third grade students aged 8. Significant outcomes from this design process involve detailed information on: (a) choice of sub-tests and item formats, (b) selection of high quality items, (c) choice and design of adaptive model, and finally, a statement on the challenges that are still to be met for such a test to function optimally. The present paper is among the first to, in an open and detailed manner, describe the development process as well as qualities and challenges of an adaptive reading screening test for students of this young age.